2020
DOI: 10.1172/jci138728
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine targeting SIVmac251 protease cleavage sites protects macaques against vaginal infection

Abstract: Authorship note: HL, RWO, and BL contributed equally to this work. FAP is deceased. Conflict of interest: ML is the inventor of patents owned by Her Majesty The Queen In Right of Canada as represented by The Minister of Health: Canada patent no. 2,833,425, "Protease cleavage site peptides as an HIV vaccine"; US patent no. 10,285,942, "Methods of inducing an immune response against HIV by administering immunogenic peptides obtained from protease cleavage sites"; and European patent no. 2,694,654, "Protease clea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 120 publications
(121 reference statements)
2
19
0
Order By: Relevance
“…After immunizations with the PCS vaccine, female MCMs were challenged repeatedly with pathogenic SIVmac251 by the intravaginal route. The data of the study showed for the first time that a vaccine targeting sequences surrounding PCS provided significant protection against repeated pathogenic SIVmac251 intravaginal challenges [84]. Notably, the PCS vaccine protected the monkeys without full-length Gag and Env immunogens.…”
Section: From Hla Epitope Analysis To Novel Hiv Vaccine Development A...mentioning
confidence: 84%
See 4 more Smart Citations
“…After immunizations with the PCS vaccine, female MCMs were challenged repeatedly with pathogenic SIVmac251 by the intravaginal route. The data of the study showed for the first time that a vaccine targeting sequences surrounding PCS provided significant protection against repeated pathogenic SIVmac251 intravaginal challenges [84]. Notably, the PCS vaccine protected the monkeys without full-length Gag and Env immunogens.…”
Section: From Hla Epitope Analysis To Novel Hiv Vaccine Development A...mentioning
confidence: 84%
“…With funding from NIH's "Innovation for HIV Vaccine Discovery" program and CIHR bridge fund, we tested the PCS vaccine approach in a nonhuman primate/SIV model [84]. Our preclinical studies demonstrated that an SIV vaccine targeting the sequences surrounding the 12 PCSs is protective.…”
Section: From Hla Epitope Analysis To Novel Hiv Vaccine Development A...mentioning
confidence: 99%
See 3 more Smart Citations